Method of Construction of pareto set At a dynamic initial data reception - S. V. Chebakov; L. V. Serebryanaya (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The many-criterial task of pareto alternatives finding at a dynamic set of initial data is considered. The general scheme of construction of partial solutions in a case when each element is formed on certain computing algorithm is presented. Concepts of dominating and dominated vectors on pareto set are defined and the algorithm of their construction is offered. The scheme of formation of partial solutions without direct comparison of alternatives is developed.